Aspects of regulation of results of intellectual activity, created under a state contract - M. V. Osipova (Современная наука и инновации)
Recently, the sphere of innovation has been actively growing. Activity in this area involves working with intellectual property. And by adding new measures to the section related to the implementation of government contracts, we can say that the state is actively studying this issue and solving possible problems. The purpose of writing the article is to study the problems in the described area. The article describes the theoretical aspects of intellectual activity, the peculiarities of regulating the rights to the results of intellectual activity, which are created within the framework of government contracts. The article also discusses the distinctive features of the management of the exclusive rights of the Russian Federation for this type of results of intellectual activity, and touches upon the problems of the execution of government contracts.